Praperadilan Kasus Korupsi SP3 dalam Perspektif Peradilan Korban - Maulana Yusuf Setiyawan (Pusat Riset dan Inovasi Nasional, 2024)
Corruption in Indonesia has spread like a virus since the 1960s and has harmed not only the victims of this crime, but also the national economy. The government is trying to eradicate such crimes, namely law enforcement, but the problem persists. Standard legal research methods were used in the current study. A statutory approach was used to consider the termination of an investigation as a basis for filing an earlier trial by a third party whose data was collected from a library review. To analyze the data, the researcher examined the materials obtained for further processing. As a result, it was revealed that there is still a huge gap between law enforcement officials and those who suffer from corruption cases. The pretrial complaint mechanism still leaves ambiguity in the hearts of victims because it has not been effective. Therefore, based on the findings, we recommend that law enforcement officials implement some serious and clear eradication mechanisms to reduce corruption and victims in Indonesia.